The show must go on: Pandemic consequences on musicians' job insecurity perception. (November 2022) - Alfarone, Irene; Merlone, Ugo
The purpose of this article is to analyze the consequences of the COVID-19 pandemic on Italian musicians' perception of job insecurity. We collected the answers of more than 200 Italian musicians, and the data showed that musicians' perception of job insecurity increased in the post-pandemic period. Furthermore, we analyzed the different impact of two objective indicators of job insecurity, the pandemic outbreak and contracts, on strains and resources. We found that contracts are a strong predictor of perceived job insecurity even after the pandemic. Social support is vital in buffering job insecurity perception, motivation is a powerful moderator of emotional exhaustion and turnover intentions, and job insecurity is strongly related to the intentions of leaving the profession. In addition, the analyses have shown that the most detrimental effects are due to subjective job insecurity rather than from its objective indicators. Finally, as this study arose from an Australian research, we provide a brief comparison of the findings.